Evidence that blood ionized calcium can regulate serum 1,25(OH)2D3 independently of parathyroid hormone and phosphorus in the rat. - Bushinsky, D A (1985)
This study asks whether arterial blood ionized calcium concentration (Ca++) can regulate the serum level of 1,25-dihydroxy-vitamin D3 [1,25(OH)2D3] independently of serum phosphorus and parathyroid hormone (PTH). We infused either PTH (bovine 1-34, 10 U/kg body wt/h) or saline into awake and unrestrained rats for 24 h, through a chronic indwelling catheter. PTH raised total serum calcium and arterial blood ionized calcium, yet serum 1,25(OH)2D3 fell from 35 +/- 6 (mean +/- SEM, n = 10) with saline to 12 +/- 3 pg/ml (n = 11, P less than 0.005 vs. saline). To determine if the decrease in serum 1,25(OH)2D3 was due to the elevated Ca++, we infused PTH into other rats for 24 h, along with varying amounts of EGTA. Infusion of PTH + 0.67 micron/min EGTA reduced Ca++, and 1,25(OH)2D3 rose to 90 +/- 33 (P less than 0.02 vs. PTH alone). PTH + 1.00 micron/min EGTA lowered Ca++ more, and 1,25(OH)2D3 increased to 148 +/- 29 (P less than 0.01 vs. saline or PTH alone). PTH + 1.33 micron/min EGTA lowered Ca++ below values seen with saline or PTH alone, and 1,25(OH)2D3 rose to 267 +/- 46 (P less than 0.003 vs. all other groups). Thus, during PTH infusion lowering Ca++ with EGTA raised 1,25(OH)2D3 progressively. There were no differences in serum phosphorus concentration or in arterial blood pH in any group infused with PTH. The log of serum 1,25(OH)2D3 was correlated inversely with Ca++ in all four groups infused with PTH (r = -0.737, n = 31, P less than 0.001), and also when the saline group was included (r = -0.677, n = 41, P less than 0.001). The results of this study indicate that serum 1,25(OH)2D3 may be regulated by Ca++ independent of PTH and serum phosphorus levels in the rat. Since 1,25(OH)2D3 regulates gastrointestinal calcium absorption, there may be direct feedback control of 1,25(OH)2D3, by its regulated ion, Ca++.